Effectiveness of prenatal breastfeeding counseling on breastfeeding practices - Ayue, Heti Ira; Oktaviani, Oktaviani (Poltekkes Kemenkes Yogyakarta, 2019)
One of the efforts to reduce infant mortality is through exclusive breastfeeding (EBF). The target of EBF coverage in the world shows a fluctuating trend that tends to decrease. One of the innovations needed to increase exclusive breastfeeding is through prenatal breastfeeding counseling. This study aims to look at the effectiveness of prenatal breastfeeding counseling on breastfeeding practice. This research used a quantitative approach using a quasi-experimental design with a post-test only control group design approach. The study was conducted in the working area of ​​the Menteng Public Health Center in Palangka Raya in March-October 2018. Samples for each group were 20 respondents who met the inclusion criteria. The data collection tool uses a questionnaire. Data analysis included univariate and bivariate (Chi-Square and Odd Ratio tests). The results of comparative testing of the effectiveness of breastfeeding counseling found a significant relationship between prenatal breastfeeding counseling with breastfeeding practice p-value = 0.025 (p <0.05) with an Odd Ratio of 0.222 which means that mothers given prenatal breastfeeding counseling have the potential to give EBF practice as much as 1 / 0.222 = 4.5 times higher than mothers who were not given counseling. Prenatal breastfeeding counseling was effective in enhancing EBF practices.